Spatial arrangement of genes, centromeres and chromosomes in human blood cell nuclei and its changes during the cell cycle, differentiation and after irradiation - Skalníková, M; Kozubek, S; Lukásová, E; Bártová, E; Jirsová, P; Cafourková, A; Koutná, I; Kozubek, M (Chromosome research, 2000)
Higher-order compartments of nuclear chromatin have been defined according to the replication timing, transcriptional activity, and information content (Ferreira et al. 1997, Sadoni et al. 1999). The results presented in this work contribute to this model of nuclear organization. Using different human blood cells, nuclear positioning of genes, centromeres, and whole chromosomes was investigated. Genes are located mostly in the interior of cell nuclei; centromeres are located near the nuclear periphery in agreement with the definition of the higher-order compartments. Genetic loci are found in specific subregions of cell nuclei which form distinct layers at defined centre-of-nucleus to locus distances. Inside these layers, the genetic loci are distributed randomly. Some chromosomes are polarized with genes located in the inner parts of the nucleus and centromere located on the nuclear periphery; polar organization was not found for some other chromosomes. The internal structure of the higher-order compartments as well as the polar and non-polar organization of chromosomes are basically conserved in different cell types and at various stages of the cell cycle. Some features of the nuclear structure are conserved even in differentiated cells and during cellular repair after irradiation, although shifted positioning of genetic loci was systematically observed during these processes.
Keywords: lidské chromozomy; Cell Nucleus; centromera; Cell Compartmentation; HL-60 buňky; hybridizace in situ fluorescenční; Centromere; buňky kostní dřeně; kompartmentace buňky; buněčné jádro; leukopoéza; lymfocyty; geny; Interphase; Genes; interfáze; lidé; HL-60 Cells; Humans; Lymphocytes; U937 Cells; Cell Cycle; In Situ Hybridization, Fluorescence; Chromosomes, Human; buněčný cyklus; Leukopoiesis; Bone Marrow Cells; U937 buňky